Walking a tightrope: ethical tensions in managing severe self-harm in a forensic mental health unit for young people - Johal, Harleen Kaur (The journal of forensic psychiatry & psychology, 2025)
While there is extensive research on how general mental health professionals respond to self-harm (SH) by adults, there is comparatively little research on the management of severe SH in forensic mental health settings for young people. This study aimed to explore how different professionals make decisions on managing SH in this population. A qualitative methodology was employed to investigate participants’ experiences. Focus groups were conducted with 14 professionals working in a UK medium-secure forensic mental health unit for young people, where severe SH is recurrent. Following the method of thematic analysis, two themes were identified. The first (‘walking a tightrope’) illustrates how professionals saw their role as allowing young people to make decisions within restrictive boundaries; how they negotiated ethical tensions between facilitating decision-making and intervening to prevent harm; and how this was perceived externally. The second theme (‘strategies employed’) describes professionals’ approaches to managing severe SH. Our findings add insight into how staff in forensic settings make complex ethical decisions, which are often concealed under the catch-all label of ‘clinical judgement’.